1992
DOI: 10.1039/p29920000523
|View full text |Cite
|
Sign up to set email alerts
|

A helical Dpg homo-peptide

Abstract: The first X-ray diffraction structure analysis of a helical homo-peptide of Caya-dipropylglycine (Dpg) has been performed for Tfa-( Dpg),-DBH monohydrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…However, more recently, detailed energy computations and x‐ray diffraction and solution conformational investigations have shown that the picture presented above is not so simple, in that Deg, Dp n g, Db nug, Dvg ( C α,α ‐divinylglycine), Dp r g ( C α,α ‐dipropargylglycine), and Dp c g ( C α,α ‐dicyclopropylglycine) (Figure 1) rich peptides can adopt either the fully extended or the helical conformation depending upon physical state (including solvent polarity) and sequence context, thus emphasizing that energy differences between these two structures, at least at the level of these residues, are small 71–90. The delicate balance between the two conformations has been confirmed by incorporation in a host sequence of a modest point defect [an Abu guest residue perturbing the regular alignment of the side chain of a (Deg) 5 homo peptide], which is enough to drastically bias the preferred conformation toward the 3 10 ‐helix 91.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recently, detailed energy computations and x‐ray diffraction and solution conformational investigations have shown that the picture presented above is not so simple, in that Deg, Dp n g, Db nug, Dvg ( C α,α ‐divinylglycine), Dp r g ( C α,α ‐dipropargylglycine), and Dp c g ( C α,α ‐dicyclopropylglycine) (Figure 1) rich peptides can adopt either the fully extended or the helical conformation depending upon physical state (including solvent polarity) and sequence context, thus emphasizing that energy differences between these two structures, at least at the level of these residues, are small 71–90. The delicate balance between the two conformations has been confirmed by incorporation in a host sequence of a modest point defect [an Abu guest residue perturbing the regular alignment of the side chain of a (Deg) 5 homo peptide], which is enough to drastically bias the preferred conformation toward the 3 10 ‐helix 91.…”
Section: Discussionmentioning
confidence: 99%
“…89 Interestingly even in the homotripeptide Tfa-(Dpg) 3 -DBH (DBH= N,N(-dibenzyl-hydrazide), all the three Dpg residues adopt helical f, c values. 90 Recent studies from our laboratory have attempted to probe the eect of local sequence variations on Dpg residue conformation.…”
Section: ±85mentioning
confidence: 99%
“…It has been reported that, with a few exceptions, 28,[52][53][54] extended conformations are favored over helical conformations when the C ␣ atom is symmetrically disubstituted with linear alkyl side chains, such as in Deg and Dpg. 23,55 On the opposite side, the helical conformation becomes more stable when the side chains are interconnected into a cyclic system, as for the cycloaliphatic residues of general formula Ac n c, with n ϭ 5, 6, 7.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In the last few years we devoted our attention to the conformational behavior of new C ␣,␣ -dialkylated residues, containing different groups of increasing bulkiness on the C ␣ atom. [23][24][25][26][27][28] In particular, the conformational preferences of Dg (C ␣,␣ -diphenylglycine) containing peptides have been recently analyzed. 29 -36 As a part of this program, we have now undertaken the study of the conformational properties of the Afc residue, which can be considered as a Dg derivative, since it contains on the C ␣ atom two phenyl rings condensed through their orto positions.…”
Section: Introductionmentioning
confidence: 99%